Employment problems in Kazakhstan (Вестник КазНУ. Серия Экономическая, 2017)
Problems of employment of the population, unemployment and labormobility is always the focus of scientific, social, political and economiclife. In its policy to establish and maintain employment Kazakhstan has gonefrom planning and decision-making techniques used by the socialist economyto a predominantly market mechanism to maintain and regulate the process.However, the economic crisis and the subsequent stop, bankruptcy and liquidationof enterprises, reducing the need for workers led to the widespread useof methods of state regulation and the maintenance of employment. Therefore,the President’s message, this problem is always current.The Message of the President NA Nazarbayev to people of Kazakhstanon January 27, 2012. “Socio-economic modernization - main directionof development of Kazakhstan” highlights the beginning of a new stageof Kazakhstan’s way for the next decade, which means new challenges tostrengthen the economy and improve the people’s welfare. This article discussesthe basic provisions of the Message. In addition to focus on the mainconclusions to regulate the economic relations of the employed population.